Cecal volvulus on top of Ladd’s band: a case report and review of literature - Mohamed Salah Ayyad; Abdallah Alqasaby; Mohamed Rezk; Ahmed Abonosier; Shaimaa Khalid; Ahmed Azam (Bulletin of the National Research Centre)
Abstract Background Cecal volvulus is a rare cause of bowel obstruction that represents a challenge in both diagnosis and management. This unique form of closed-loop obstruction occurs due to a twist in the mesentery with subsequent dilatation of the cecum. As a result of the massive distension of the large bowel, many radiologists find it difficult to recognise the signs suggestive of cecal volvulus. In this article, we highlight the role of imaging in the management of this form of bowel obstruction. Case presentation A thirty-six-year-old female patient presented to our emergency department with symptoms of acute abdomen. Imaging revealed a massively dilated large bowel loop in an abnormal distribution in the centre of the abdomen with a whirlpool in the mesentery. Cecal volvulus was suspected. Surgical exploration confirmed the diagnosis, and an abnormal band connected to the caecum (Ladd’s band) was also identified. The patient underwent division of the band with ileo-transverse colostomy. Unfortunately, the patient passed away due to cardiorespiratory failure two days after the operation. Conclusions The radiologist should always consider cecal volvulus in the differential diagnosis of closed-loop obstruction, particularly at a young age. A hypermobile caecum on imaging may suggest Ladd's band, even without signs of malrotation. All relevant items should be addressed when reporting bowel obstruction cases.